Development of Learning Tools by Applying The MASTER Plan Technique Based on A Scientific Approach to Improve Student Learning Outcomes on Number Pattern Material - Herni Purnamawati; Atma Murni; Sehatta Saragih (Department of Mathematics Education University of Muhammadiyah Malang, 2020)
This research is motivated by the lack of optimal learning outcomes of students due to the lack of learning devices that are considered being able to train students’ abilities in solving problems. The purpose of this study is to develop mathematics learning tools that meet the validity, practicality, and effectiveness requirements to improve the learning outcomes of grade VIII students of SMP / MTs on material number patterns. The development model used is the ADDIE model for designing learning systems. The instruments used were syllabus validation instruments, RPP, LKPD, practicality instruments and effectiveness instruments. The technique used is the technique of collecting observation data, interviews, questionnaire documentation and tests. Mathematics learning to use the MASTER Plan technique based on a scientific approach is already valid with the results of syllabus validation 84.25%, RPP 90.30%, LKPD 86.50%. This learning device fulfills the practical requirements for large group trials with an average of 93.52% results and an average student questionnaire response rate of 95.66%. The use of effective learning tools to improve student learning outcomes for KKM achievement is 83.33%.